Selective Omnidirectional Magnetic Resonant Coupling Wireless Power Transfer With Multiple-Receiver System - Zhongyu Dai (IEEE Access, 2018)
Magnetic resonant coupling (MRC) wireless power transfer (WPT) technology provides a novel solution to the tricky power-charging issue of densely connected sensor devices in the age of Internet of Things. Due to the cost and space constraints, the one-to-one MRC WPT is not suitable for charging the large number of sensor devices. The one-to-many MRC WPT requires less cost and space, but all receivers receive the power emitted from the transmitter disregarding the receivers' needs, which will lead to the accelerated aging even damage or malfunction of the receivers. In this paper, we propose a selective omnidirectional MRC WPT with multiple-receiver system. The power transmitted by an omnidirectional transmitter composed of three orthogonal circular coils will be received by any receiver located nearby. As the number of the transmitters reduces, the cost and space declines. Based on the band pass filter principle, the receivers selectively acquire the power at a designated frequency, which improves the energy efficiency and increase equipment service life. Moreover, for the proposed model, its magnetic field distribution of the simulation and physical experiments are carefully designed and performed, and their results are examined and analyzed in detail. They all confirm the capabilities of selective power transferring and the omnidirectional power transfer of the MRC WPT.